Perlindungan Hukum Terhadap Penumpang Dan Barang Yang Diangkut Oleh Kereta Api - Dicky Arifianto; Gurnadi Lie; Moody Rizqy Syailendra (Jurnal Ilmiah Wahana Pendidikan, 2023)
Transportation is a vital means and key to accelerating the wheels of the economy, strengthening solidarity and unity and having an impact on all parts of the existence of the nation and state. When compared to other modes of transportation, trains offer advantages such as their capacity to carry large numbers of passengers, energy saving, space saving, and low levels of contamination. Trains with passengers, where PT. The train binds itself to deliver passengers to their destination safely, while the passenger pays transportation costs, so that if the passenger does not arrive safely at his destination and causes a loss, the railroad company must be held responsible. This study aims to examine and analyze the legal responsibility of the railroad company in the event of a loss to cargo in the operation of transportation by train and legal protection for passengers in the event of an accident in the operation of transportation by rail. The methodology used is normative juridical. The results of the research are that when transporting goods by train, PT KAI is not responsible for compensation to service users for losses caused by force majeure or overmacht. PT KAI as the organizer of the administration of rail transportation must be responsible for travelers in the event of an accident, as long as the accident is the result of unacceptable rail activity. However, the carrier is released from the obligation to provide compensation if he can prove his innocence.